Investigation of wake wash in the towing tank - Abdul Ghani, Mohamad Pauzi; Ahmad Sabki, Ahmad Fuaad (Universiti Teknologi Malaysia, 2005)
In recent years, the demand for high speed craft has increased significantly. The wave resistance plays an important role in total resistance and power prediction, which influence the design. Additionally, wake wash generated by high-speed crafts is also important to the design concept due to its impact on safety and environment such as beach/bank erosion, risk to people on shore and small boats in harbours and changes in the local ecology. This report describes about the investigation of wake wash developed from high speed marine craft in the towing tank. The data acquisition system and wave probe for wake wash measurement has been developed.